Behavioral Activation as a Principle-Based Treatment: Developments from a Multi-Site Collaboration to Advance Adolescent Depression Treatment. Issue 1 (2nd January 2023) - Jenness, Jessica L.; DeLonga, Kathryn; Lewandowski, R. Eric; Spiro, Carolyn; Crowe, Katherine; Martell, Christopher R.; Towbin, Kenneth E.; Stringaris, Argyris; McCauley, Elizabeth
ABSTRACT: Adolescent depression is a serious and debilitating disorder associated with lifelong negative outcomes, including heightened risk for recurrence into adulthood, psychiatric comorbidities, and suicide. Among evidence-based treatments for adolescents, psychotherapies for depression have the smallest effect sizes of all psychiatric conditions studied. Advancing care for depression in adolescents is complex due to the heterogeneity in etiology and co-occurring difficulties among youth presenting with depression symptoms. This and a companion paper (Lewandowski et al., 2022) draw on a recent multisite collaboration that focused on implementing depression treatment for adolescents within clinical and research contexts. Specifically, this paper will review our work adapting behavioral activation (BA) as a principle-based framework to improve effectiveness and efficiency of depression treatment used within clinical and research settings in academic medical centers. Piloted adaptations include the use of BA principles to address idiographic drivers of depression and in-session BA "exposures" to illustrate BA principles. Case vignettes illustrate these adaptations of BA to address adolescent depression in the context of co-occurring difficulties.